Antioxidant Effects of Myo-Inositol Improve the Function and Fertility of Cryopreserved Boar Semen - Rana Osman; Seongju Lee; Areeg Almubarak; Jae-Ik Han; Il-Jeoung Yu; Yubyeol Jeon (MDPI AG, 2023)
During cryopreservation, sperm undergoes structural and molecular changes such as ice crystal formation, DNA fragmentation, and reactive oxygen species (ROS) production, leading to decreased sperm quality after thawing. Antioxidants play a crucial role in preventing these damages, both in vivo and in vitro. One potent antioxidant is myo-inositol, known for its protective effects on sperm against ROS. This study aimed to investigate the protective effect of myo-inositol on cryopreserved boar semen. The semen was diluted, cooled, and cryopreserved using a BF5 extender. It was then divided into five groups: control and different concentrations of myo-inositol (0.5, 1, 1.5, and 2 mg/mL). The post-thaw evaluation included assessments of motility, viability, acrosome integrity, mitochondrial membrane potential (MMP), caspase activity, gene expression, ROS levels, apoptosis, and IVF with treated semen. Results showed that myo-inositol at 0.5 mg/mL improved motility, acrosome integrity, and fertilization ability. It also reduced the expression of pro-apoptotic genes and increased SMCP expression. Lower concentrations also demonstrated improved viability and reduced apoptosis and ROS levels. In conclusion, myo-inositol treatment during cryopreservation improved sperm quality, reduced apoptosis and ROS levels, and enhanced fertility rates in boar semen.